Improving teamwork skills and enhancing deep learning via development of board game using cooperative learning method in Reaction Engineering course - Azizan, M.T. (Elsevier B.V., 2018)
To produce well-rounded students with excellent teamwork skills and creativity, one of the teaching strategies that can be adopted in engineering education is cooperative learning. This study aims to enhance creativity, deep learning and improve teamwork skills among the third-year chemical engineering students using cooperative learning strategy. Complex instruction method is adopted by instructing the students to develop a board game and embed technical based questions, which are related to kinetic and reactor design subject (KRD) and other two courses, as part of the integrated project. The reflections from the students, the findings from the survey and the evaluation of the studentsâ outputs, suggested that though they enjoyed the activity, it was a challenging and a complex task, which in turn provoked their thoughts, creativity and made them acquired teamwork skills. Â© 2017 Institution of Chemical Engineers